2007
DOI: 10.1590/s0103-84782007000100039
|View full text |Cite
|
Sign up to set email alerts
|

Morfometria do oviduto de poedeiras comerciais semipesadas submetidas a diferentes métodos de muda forçada

Abstract: Morphometry of the oviduct of the brown egg layer hens submitted different methods of molt induction RESUMO INTRODUÇÃOA muda de penas é um processo natural de todas as aves. As aves silvestres fazem muda de penas anualmente. Nestas aves, a produção de ovos é pequena e a muda está associada ao ciclo reprodutivo. Contudo, o processo de muda vai além da substituição de penas. Estudos revelam que um significativo incremento da taxa de metabolismo, aumento da síntese de algumas proteínas, osteoporose, perda de gord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(7 reference statements)
0
4
0
4
Order By: Relevance
“…The lack of effect of induced-molting methods on relative weight of the oviduct (p < 0.05) was also observed by Araújo et al (2007), who evaluated different molting methods (California method, diet with high zinc, low calcium or low sodium diets) and did not detect any influence of the treatments on this parameter.…”
Section: Use Of Nicarbazin Salinomycin and Zinc Oxide As Alternativementioning
confidence: 59%
“…The lack of effect of induced-molting methods on relative weight of the oviduct (p < 0.05) was also observed by Araújo et al (2007), who evaluated different molting methods (California method, diet with high zinc, low calcium or low sodium diets) and did not detect any influence of the treatments on this parameter.…”
Section: Use Of Nicarbazin Salinomycin and Zinc Oxide As Alternativementioning
confidence: 59%
“…Except for the quails submitted to the 25% BWL fasting, all results are consistent with El-Deek & Al-Harthi (2004), who, studying induced molting in hens, observed no difference in ovary weight, oviduct weight and length of hens fed 20,000 ppm zinc oxide in the feed, submitted to feed restriction, or submitted to fasting. Araújo et al (2006), analyzing the ovary and the oviduct on different days post-molting, concluded that reproductive system biometrics was not different in layers submitted to fasting or to the method of 20,000 ppm zinc oxide dietary inclusion. Quails molting by fasting at 25% BWL did not present satisfactory reduction of oviduct length, ovary weight, oviduct weight, and reproductive system weight parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed by Berry & Brake (1991), who compared fasting to the dietary supply of 2,000 ppm zinc oxide as forced-molting method until 30% weight loss, and 1.18% oviduct weight relative to live weight when zinc oxide was used. One of the most important factors of induced molting is body weight loss, resulting in follicle development arrest and atresia (Araújo et al 2007), which will ensure optimal performance during the second laying cycle. Relative organ weights evaluated when hens were sacrificed after the post-molting period were not influenced by the treatments ( Table 5), showing that the amino acid levels supplied were sufficient to recover the weights of the reproductive organs, liver, and pancreas, thereby promoting good results during the second laying cycle.…”
Section: Lysine and Methionine + Cystine For Laying Hens During The Pmentioning
confidence: 99%